SISTEM PENDUKUNG KEPUTUSAN DALAM MEMILIH AIR CONDITIONER (AC) DENGAN METODE SIMPLE ADDITIVE WEIGHTING - Felix .; Anton Siswo Raharjo Ansori (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2022)
Sales of Air Conditioners (AC) in Indonesia have increased due to the increase in temperature in Indonesia every year. This makes the use of electrical energy in Indonesia also increasing, excessive use of electricity can cause problems such as global warming. One solution to save on the use of electrical energy is to choose the right air conditioner as needed so that electricity use can be more efficient. To assist buyers in choosing air conditioners because the types of air conditioners are increasingly varied in terms of price, model and quality, a decision support system is needed that can assist buyers in choosing an air conditioner that suits their needs. The method used in this research is simple additive weighting (SAW) method. SAW is a decision support system method that determines the best alternative by calculating the weighted sum of the performance ratings on all alternatives across all criteria. Based on the results of the tests in this study, using the simple additive weighting method can help buyers in choosing an air conditioner that is in accordance with the choices that have been determined by the buyer using price, PK, power, cooling capacity, weight, warranty as comparison criteria. Keywords: Air conditioner, Choosing the right air conditioner, Decision support system, Simple additive weighting (SAW), Sales of air conditioners, Use of electrical energy